Characterization of population genetic structure of hereditary transthyretin amyloidosis in Bulgaria. (2nd October 2021) - Pavlova, Zornitsa; Sarafov, Stayko; Todorov, Tihomir; Kirov, Andrey; Chamova, Teodora; Gospodinova, Mariana; Tournev, Ivailo; Mitev, Vanyo; Todorova, Albena
Abstract: The hereditary transthyretin amyloidosis (ATTRv amyloidosis) is an autosomal dominant genetic disease characterized by amyloid formation in different tissues due to pathogenic variants in the TTR gene. Great heterogeneity in the penetrance and manifestation of ATTRv amyloidosis is observed. In Bulgaria, the most common TTR pathogenic variant is Glu89Gln . Other TTR pathogenic variants are also found – Val30Met, Ser77Phe, Gly47Glu and Ser52Pro . There is a proven founder effect for the Glu89Gln variant, thus the aim of the present study is to investigate the founder effect for the other TTR pathogenic variants in Bulgaria. Haplotype analysis was performed by using microsatellite markers close to the TTR gene. DNA samples from ATTRv amyloidosis patients and their healthy relatives were analyzed. Theoretical haplotype reconstruction was done with Arlequin v.3.01 software. The age of the most recent common ancestor (hypothetical founder) for the studied variants was calculated with the DMLE 2.2 software. In addition, DBS screening among 100 Roma newborns was done for the Gly47Glu TTR variant via direct Sanger sequencing. The reconstructed haplotypes of the patients were compared to their healthy relatives and to a control group of 40 healthy individuals. The results showed a possible founder effect for each of the studied variants. The Val30Met haplotype was compared to published haplotype data for this variant and no similarity was found. The result from the DBS screening showed no pathogenic TTR variants in exon 2 of the gene, so we considered the presence of the Gly47Glu variant in our population a sporadic event. With this study, we succeeded to gain a more complete picture of the population genetics of ATTRv amyloidosis in Bulgaria and made another step towards a more detailed understanding of the disease epidemiology.